A survey of traditional and faith healers providing mental health care in three sub-Saharan African countries (2019)
Background: Traditional and faith healers constitute an important group of complementary and alternative mental health service providers (CAPs) in sub-Sahara Africa. Governments in the region commonly express a desire to integrate them into the public health system. The aim of the study was to describe the profile, practices and distribution of traditional and faith healers in three sub-Saharan African countries in great need for major improvements in their mental health systems namely Ghana, Kenya and Nigeria. Materials and methods: A mapping exercise of CAPs who provide mental health care was conducted in selected catchment areas in the three countries through a combination of desk review of existing registers, engagement activities with community leaders and a snowballing technique. Information was collected on the type of practice, the methods of diagnosis and the forms of treatment using a specially designed proforma. Results: We identified 205 CAPs in Ghana, 406 in Kenya and 82 in Nigeria. Most (> 70%) of the CAPs treat both physical and mental illnesses. CAPs receive training through long years of apprenticeship. They use a combination of herbs, various forms of divination and rituals in the treatment of mental disorders. The use of physical restraints by CAPs to manage patients was relatively uncommon in Kenya (4%) compared to Nigeria (63.4%) and Ghana (21%). CAPs often have between 2- to 10-fold capacity for patient admission compared to conventional mental health facilities. The profile of CAPs in Kenya stands out from those of Ghana and Nigeria in many respects. Conclusion: CAPs are an important group of providers of mental health care in sub-Saharan Africa, but attempts to integrate them into the public health system must address the common use of harmful treatment practices.